Pengaruh Inovasi Produk dan Brand Ambassador EXO Terhadap Keputusan Pembelian: Studi Kasus Terhadap Konsumen Scarlett Whitening di Tangerang Selatan - Novita Ramadayanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of product innovation and brand ambassador to purchasing decisions Scarlett Whitening body lotion tube products in South Tangerang. Scarlett Whitening, a local Indonesian beauty brand, is known for a variety of skin care products such as body lotions, scrubs, scrubs, serums, and creams that aim to brighten and maintain healthy skin. With the motto